Board Evaluation Practices Review: A First Glimpse of Philippine Listed Banks and Holding Companies - Pho, Debbie Chua Bun (Philippine Management Review, 2023)
According to Kaur and Vij (2017), board effectiveness plays a crucial role in the growth and sustainability of a company. To better deal with the growing intricacies and uncertainty in the business landscape, the role of the board has significantly shifted from mere monitoring/control to one that provides strategic value and competitive advantage for the firm they serve. This development has elevated the importance of board evaluations. Periodic board evaluation is a valuable development tool that should go beyond compliance purpose. The genuine desire to build high-performing boards that can effectively navigate, anticipate, and meet the growing challenges in its external corporate environment must be its goal. This exploratory study aims to determine the state of compliance of board evaluation among Philippine listed banks and holding companies. The findings are quite encouraging as majority of these banks and holding companies are compliant, except for the engagement of external facilitator. However, does high compliance mean that boards are becoming more effective? Avenues for improvement abound, and the future evolution of board evaluation practices lies heavily in the creation of correct awareness among regulators, companies, directors, and other stakeholders on the proper objective, design, and execution of this essential governance tool to ensure that maximum results are attained. The establishment of accreditation criteria for external facilitators may also become essential once the demand for their services on board evaluation increases.